2017
DOI: 10.1183/13993003.00006-2017
|View full text |Cite
|
Sign up to set email alerts
|

IFN-α/IFN-λ responses to respiratory viruses in paediatric asthma

Abstract: We read with interest the paper by BERGAUER et al. [1] on innate immune responses to viral infection in paediatric asthma. The paper confirms previous reports on impaired interferon responses in stable asthma [2-4], but describes a hyperactive interferon production during asthma exacerbations associated with rhinovirus infection. The authors conclude that, despite impaired immune condition at stable state, the ability to upregulate type I interferons during the acute phase is preserved in asthmatic children. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 5 publications
5
48
2
1
Order By: Relevance
“…Our results suggest that IFN-β and IFN-λ production is altered during virus-induced exacerbations in asthmatic children. Compared to our study, the population differs from that of Bergauer et al by the age and also the severity of the exacerbation [11]. Furthermore, their results seems to be inconsistent on a larger cohort.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results suggest that IFN-β and IFN-λ production is altered during virus-induced exacerbations in asthmatic children. Compared to our study, the population differs from that of Bergauer et al by the age and also the severity of the exacerbation [11]. Furthermore, their results seems to be inconsistent on a larger cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, patients infected with hRV appeared to display the same impairment (data not shown). In contrast, Bergauer et al recently reported that IFN-α levels were markedly increased in a small cohort of hRV-infected symptomatic asthmatic children (4.8 ± 0.64 years) as compared with infected but asymptomatic patients whereas IL-29 synthesis remains unchanged [11]. Our results suggest that IFN-β and IFN-λ production is altered during virus-induced exacerbations in asthmatic children.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…28,32,47 The role of atopy is perplexing; Baraldo et al 34 showed that deficient interferon production was a feature of atopic asthmatic, nonatopic asthmatic, and nonasthmatic atopic children, 34 and studies focusing on allergic rhinitis without asthma have produced mixed results, 4,52 furthering the debate about whether it is asthma or atopy (or both) that drives this defect. Some argue that there is controversy regarding interferon deficiency in asthmatic patients because studies investigating interferon responses in patients with stable disease 53 or during AEs in vivo 54,55 find increased rather than decreased interferon levels in asthmatic patients. However, we would argue that studies of interferon levels in vivo will be confounded by differences in viral loads and that if one wishes to investigate the presence of interferon deficiency in a disease state, this can only be done by infecting cells with a standardized quantity of virus ex vivo or stimulating cells with a standard quantity of a viral mimic ex vivo.…”
Section: Limitations and Controversiesmentioning
confidence: 99%
“…All methods in this study were performed in accordance with the relevant guidelines and regulations Two cohorts of preschool children (aged 4-6 years) with and without asthma were analysed. The recruitment of the subjects, inclusion and exclusion criteria, as well as the time-scale for clinical visits and data collection, have been described recently [24][25][26], and patient characteristics are reported in Table 1.…”
Section: Human Studiesmentioning
confidence: 99%